Analisis Penentuan Batas Aman Ground Vibration Akibat Kegiatan Peledakan Terhadap Kestabilan Lereng Highwall Penambangan Pit 13 West PT. Multi Harapan Utama, Samarinda, Kalimantan Timur - Diky Canima; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Blasting activity is an activity that aims to destroy the rock that is not able to diripping, but as a result of blasting activities will cause vibrations that disturb the surrounding environment including slope stability. After opsevation and processing the data it obtained the actual value of the safety factor (SF) in March at 2.204 dry conditions, the condition of half saturated 1,793 and 1.386 water saturated conditions. SF that influenced most Amaks ie 0.0267 g with the value of the safety factor under dry conditions 2.114; 1.716 half-saturated conditions; and 1.324 water saturated conditions. Next to find out the value determination of ground vibration safe limits due to blasting activities for slope stability, vibration testing was carried out with the result Amaks 0.398 g FK value of 1.279 in dry conditions with 2 meters, Amaks 0.216 g FK value 1.2284 half-saturated conditions with a distance of 4 meters, Amaks 0.0357 g value FK 1.303 saturated conditions with a distance of 6 meters. Furthermore, this value is used as a recommended value for vibration safe limits due to blasting of slope stability.